1987
DOI: 10.1099/0022-1317-68-4-1093
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Delayed Type Hypersensitivity to Herpes Simplex Virus Type 1 Following Immunization with Anti-idiotypic Antibody: an Example of Split Tolerance

Abstract: SUMMARYIntraperitoneal (i.p.) immunization with herpes simplex virus type 1 (HSV-1) or an anti-idiotypic antibody (anti-id C) prepared against a monoclonal antibody specific for glycoprotein C of HSV-1, tolerizes mice for an HSV-I delayed type hypersensitivity (DTH) response. This tolerization could be adoptively transferred to naive Xirradiated mice by splenic T cells, and was specific for HSV-1 DTH. Thus, DTHtolerized mice responded to vaccinia virus or HSV-2 challenge, while remaining tolerized for HSV-1 DT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1989
1989
1993
1993

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
(23 reference statements)
0
4
0
Order By: Relevance
“…Thus, in the HSV system, several approaches result in a negative DTH reaction but a positive response in all other measured aspects of immunity. This so-called split tolerance can be produced either by immunizing mice with virus by the intravenous (24), intraperitoneal (10), or intracameral (32) route or by exposure of mice to certain anti-idiotype reagents (11). In this latter circumstance, we have demonstrated that exposure of mice to a heterologous anti-idiotype serum produced against a monoclonal anti-glycoprotein C antibody causes a suppressor-cell-mediated inhibition of the DTH reaction to HSV.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, in the HSV system, several approaches result in a negative DTH reaction but a positive response in all other measured aspects of immunity. This so-called split tolerance can be produced either by immunizing mice with virus by the intravenous (24), intraperitoneal (10), or intracameral (32) route or by exposure of mice to certain anti-idiotype reagents (11). In this latter circumstance, we have demonstrated that exposure of mice to a heterologous anti-idiotype serum produced against a monoclonal anti-glycoprotein C antibody causes a suppressor-cell-mediated inhibition of the DTH reaction to HSV.…”
Section: Discussionmentioning
confidence: 96%
“…Anti-Id antibodies to MAbs against BHV-1 gl (16) and gIV (31,35) and MAbs against a human cytomegalovirus envelope protein (21) stimulated production of virus-neutralizing anti-anti-Id antibodies in mice. However, anti-Id antibodies to herpes simplex virus envelope glycoproteins either generated a dose-dependent delayed-type hypersensitivity (11) or induced immune suppression, leading to increased viral pathogenicity (22,25).…”
Section: Resultsmentioning
confidence: 99%
“…The mouse ear model mimics closely this pathogenesis of primary disease (Hill et al 1975;Wildy, 1985). In contrast the lethal intraperitoneal infections used by previous workers to evaluate HSV-specific CTL (Sethi et al 1983) involves an atypical pathogenesis, including nephritis, viremia (Renis et al 1976) and the induction of suppressor cells specific for DTH (Lathey et al 1987;Nash and Ashford, 1982) . Consequently, an interpretation that CTL subserve protection only if they also release IFN-"( may only hold true in the intraperitoneal infection model, but it may not be the mechanism by which virus-specific CTL control infections of epithelia or sensory nerves.…”
Section: Activity Of Ctl In Vivomentioning
confidence: 95%